2007
DOI: 10.1177/1049731506293971
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Evaluation of Multidimensional Treatment Foster Care: Effects on School Attendance and Homework Completion in Juvenile Justice Girls

Abstract: Despite growing evidence that child welfare youth are at increased risk for juvenile delinquency, little is known about gender-specific processes and effective treatment programs for girls. Multidimensional Treatment Foster Care (MTFC), an empirically validated intervention for child welfare and juvenile justice populations, has demonstrated efficacy in reducing arrest rates in delinquent boys and girls. In this study, the efficacy of MTFC on school attendance and homework completion was examined in juvenile j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 28 publications
3
71
2
Order By: Relevance
“…Findings showed that effects found at 1 year (Leve et al, 2005) were maintained at the 2-year assessment with a slightly larger effect size, and that trajectories of reductions across the course of the study were significantly larger for MTFC. Age predicted delinquency outcomes as well, with younger girls showing more vulnerability than older girls.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Findings showed that effects found at 1 year (Leve et al, 2005) were maintained at the 2-year assessment with a slightly larger effect size, and that trajectories of reductions across the course of the study were significantly larger for MTFC. Age predicted delinquency outcomes as well, with younger girls showing more vulnerability than older girls.…”
Section: Discussionmentioning
confidence: 89%
“…In comparison, 93% of girls aged 13-19 living in the region were Caucasian (U.S. Department of Commerce, 1992). Additional demographic information is in Leve et al (2005). There were no group differences on the rates or types of pre-baseline offenses or on other demographic characteristics.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silverthorn and Frick (1999) theorized such socialization may include both parental and school-based manifestations and may discourage external expression of girls' antisocial behavior. In a randomized evaluation of an alternative juvenile justice program, Leve and Chamberlain (2007) found girls' participation in homework to play a predictive role in outcomes for girls in the justice system; these authors note similar findings by Fergusson and associates (Fergusson, Swain-Campbell, & Horwood, 2002) and note that engagement in school may help deter delinquency among girls.…”
Section: Residential and School Mobilitymentioning
confidence: 53%
“…At 1-year follow-up MTFC youth had spent 60% fewer days in lock-up than control youth in group-care (Chamberlain & Mihalic, 1998). And MTFC is positively correlated with better school attendance, improved homework completion, and less time spent in restrictive settings (Chamberlain & Mihalic, 1998;Leve & Chamberlain, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 98%